Theoretical and experimental analysis of the backward extrusion process with a rotational die of AZ31 alloy - P. Szota; S. Mroz; A. Stefanik; K. Laber; R. Mola (Metalurgija, 2021)
In this work theoretical and experimental analysis of the backward extrusion with a rotary die of the AZ31 alloy has been performed. The modification of the classical extrusion was based on the use of a rotary die. The results of theoretical research have confirmed that the use of the modified backward extrusion causes the appearance of shear stress in deformed material, which could affects the activation of additional mechanisms of deformation. The numerical modelling of the rotating extrusion of AZ31 alloy has been conducted by using the computer program Forge®. The experimental tests were carried out in the conditions of the STD 810 torsion plastometer using newly designed tools.